Study guides

☆☆

Q: What is the answer for 8t plus 5 equals 6t plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

t=-2

(6t - 1) / 69 = 1 6t - 1 = 69 6t = 70 t = 70 / 6

6t2+25+11 = (3t+11)(2t+1) when factored Use the quadratic equation formula.

Without an equality sign it can not be considered to be an equation and the plus or minus values of 56t, 1 and 6 have not been given

(1, 1)

Related questions

t=-2

t=1

8t^2 - 11t - 4

15t = 17 + 8t -24 15t - 8t = 17 - 24 7t = -7 t = -1

-(t(3t + 1)(t - 8))

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

Since 1 ton is equal to 2,000 lb, 8T is equal to 16,000 lb.

-3t3 + 23t2 + 8t = -t(3t2 - 23t - 8) = -t(3t + 1)(t - 8)

(6t - 1) / 69 = 1 6t - 1 = 69 6t = 70 t = 70 / 6

(t + 7)(t - 1)

12(t+6)+8=4(2t-1)+2t 12t+72+8=8t-4+2t 12t-2t-8t=-72-8-4 2t=-84 2t/2=84/2 t=42

t=3/2 or t=2 1/2

People also asked